Analisa Pengaruh Kuat Arus Pengelasan Gmaw Pada Pengujian Impak Baja AISI 1050 - Zainal Fakri; Bukhari Bukhari; Nawawi Juhan (Politeknik Negeri Lhokseumawe, 2019)
GMAW welding is a welding process that uses CO2 gas as a weld metal protective media from the influence of outside air. This welding uses a heat source from electrical energy that is converted or converted into heat energy. While the AISI 1050 steel plate is steel which has a carbon content of 0.50% so it is classified as medium carbon steel. This steel is widely used in the market because it has many advantages, one of which is having good weldability (machinability), good wear resistance (wear) and good mechanical properties as well. This study aims to determine the shock strength (impact) on the results of welding using the charpy method in the GMAW welding process against AISI 1050 steel with seam 70 ° V angle. Current variations used in this welding process are 100, 120 and 140 Amperes. From the tests that have been done, it is known that the highest shock strength (impact) at 100 Amperes current produces a toughness value of 2.36 joules / mm². While the lowest impact test results at a current of 120 Amperes produce a toughness value of 2.02 joules / mm². The results of the fracture form after the impact testing process show that the specimen at 100 Amperes current has a ductile fracture. While at currents of 120 and 140 Amperes the mixture is broken.. Keywords : GMAW Welding, Impact Testing, Tough Value, Impack Test AbstrakPengelasan GMAW adalah suatu proses pengelasan yang menggunakan gas sebagai media pelindung weld metal dari pengaruh udara luar. Pengelasan ini menggunakan sumber panas dari energi listrik yang dirubah atau dikonversikan menjadi energi panas. Sementara plat baja AISI 1050 merupakan baja yang memiliki kadar karbon 0.50% sehingga tergolong dalam baja karbon sedang. Baja ini banyak digunakan di pasaran karena memiliki banyak keunggulan salah satunya adalah mempunyai sifat mampu las yang baik (machinability), wear resistance-nya (keausan) baik dan sifat mekaniknya yang baik juga. Penelitian ini bertujuan untuk mengetahui kekuatan kejut (impak) pada hasil pengelasan dengan menggunakan metode charpy pada proses las GMAW terhadap baja AISI 1050 dengan kampuh V sudut 70º. Variasi arus yang digunakan dalam proses pengelasan ini yaitu 100, 120 dan 140 Ampere. Dari pengujian yang telah dilakukan, diketahui bahwa kekuatan kejut (impak) tertinggi pada arus 100 Ampere menghasilkan nilai ketangguhan sebesar 2.36 joule/mm². Sementara hasil pengujian impak terendah pada arus 120 Ampere menghasilkan nilai ketangguhan sebesar 2.02 joule/mm². Hasil bentuk patahan setelah proses pengujian impak menunjukkan benda uji pada arus 100 Ampere mengalami patah ulet. Sementara pada arus 120 dan 140 Ampere mengalami patah campuran.Kata Kunci: Pengelasan GMAW, Pengujian Impak, Nilai Ketangguhan, Uji Impack